SISTEM PAKAR DIAGNOSA JENIS KULIT WAJAH MENGGUNAKAN METODE FORDWARD CHAINING (STUDI KASUS : DITUJUKAN PADA KONSUMEN WARDAH) - Guruh Sasmita (Jurnal Informatika Kaputama (JIK), 2020)
The role of facial beauty experts is very important to identify the type of facial skin and provide solutions in the form of treatment recommendations using the right skincare products for each type of facial skin. The thing that is often complained of by the public when performing treatments is the small number of beauticians because not every region has a beauty clinic and the limited time the beautician doctors cause a long queue when going to a beauty clinic. From this, an expert system is needed to help provide solutions by building an expert system that can identify the type of facial skin by including treatment solutions. The Fordward Chaining method carries out tracking that starts with input information, and then tries to draw conclusions. From this research will produce a web-based application to diagnose skin types and solutions to any skin problems and display the name of the product recommended for treatment.